Effect of Co-60 gamma-ray irradiation on electrical properties of Ti/Au/GaAs1-xNx Schottky diodes - Teffahi, A.; Hamri, D.; Mostefa, A.; Saidane, A.; Al Saqri, N.; Felix, J.F.; Henini, M. (Elsevier, 2016)
Current-voltage (I-V), capacitance-voltage-frequency (C-V-f) and conductance-voltage-frequency (G/ω-V-f) measurements at room temperature are used to study 50 kGy 60Co γ-ray electrical properties irradiation dependence of Ti/Au/GaAs1−xNx Schottky diodes with 0.2%; 0.4%; 0.8% and 1.2% nitrogen dilution. This γ-ray irradiation induces a permanent damage that has increased ideality factor and series resistance for all samples. It was accompanied by a decrease in Schottky barrier height with nitrogen content up to 0.4%N and remained constant thereafter. Radiation was also found to degrade the reverse leakage current.